The past three decades of plant physiology in Hungary - Erdei, László (Acta Biologica Szegediensis, 2011)
This retrospective paper describes the emergence and development of the organizations of plant physiologists and their activities in the last three decades in Hungary. It is concluded that the Federation of European Societies of Plant Physiology (FESPP) initiated the birth of the Hungarian Society for Plant Physiology and exerted great impact on its activities in participating the FESPP congresses, in organizing the congresses of the Hungarian Society and also the 12th FESPP Congress in Budapest. The past 30 years witnessed the transition of the traditional plant physiology into the postgenomic era, which brought more intense co-operation between plant scientists in a modernized form of the organized framework of research and development of integrated plant biology.